Lingkungan Kampus menuju Pembiasaan Baru selama Kondisi Pandemi Covid-19 - Asnita Frida Sebayang; Asri Nuranisa Dewi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2020)
After the outbreak of the Covid-19 pandemic in Indonesia, the government issued a new policy of learning, working, and worshiping from home. This pandemic has created a crisis that has hit many sectors, one of which is education. Culture shock is a hot issue for teachers and students in facing this new educational situation. Learning using an E-learning system must be done without considering the existing limitations. The impact on tertiary institutions seems not to have been revealed much because it is often considered quite adaptive to the various changes that exist. This study used a quantitative approach with two times data collection, which is based on random sampling of all active students at the Faculty of Economics and Business, UNISBA and tracing the severe economic impacts on the student’s family environment using a survey instrument. The problems that dominate students are internet network, limited internet data, and the economic condition of the family in carrying out learning activities from home. This condition can open the possibility of an increase in the level of pressure focusing on learning and problems with the decline in the family economy.